Learning Action Cell (Lac) Sessions on Professional Development and Their Impact on Quality Instruction - Rosalina T. Detuya; Rufino T. Tudlasan Jr (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2026)
This research examined the influence of Learning Action Cell (LAC) sessions on the professional development of teachers at Subangdaku Elementary School during the 2025–2026 school year, serving as a basis for crafting a Professional LAC Development Plan. Specifically, it assessed the implementation of LAC sessions in terms of active learning, content focus, duration, coherence, and collective participation. It measured their impact on teachers’ professional competence across the domains of curriculum, content, pedagogy, assessment, and integration, guided by the Philippine Professional Standards for Teachers (PPST). Utilizing a descriptive-correlational design, data were gathered from seventy-five (75) teacher-respondents through a validated survey questionnaire and analyzed using mean, standard deviation, and correlation analysis. Findings revealed that most teachers were female (88%), aged 41–50 (44%), and highly experienced, with an average of 22.68 years in service. They demonstrated strong engagement in professional learning, with 60% having attended more than 51 hours of training. Teachers strongly agreed that LAC sessions enhance active learning (AWM = 4.61), are content-focused (4.54), and promote collective participation (4.57). A significant relationship was found between LAC sessions and teacher competence (r = 0.661, t = 7.258, p < 0.05), indicating that the implementation of LAC has a positive influence on professional growth. Teachers also exhibited high competence across PPST domains (overall AWM = 4.33). The study concludes that LAC sessions effectively enhance teachers’ professional competence and recommends the institutionalization of a Professional LAC Development Plan to ensure regular scheduling, relevant content, and sustained administrative support for continuous teacher development.